Alignment of corporate social responsibility with corporate strategy in companies listed on the Johannesburg Stock Exchange Socially Responsible Investment (SRI) index - Babb, Sarah (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2010.